POLA KUMAN DAN SENSITIVITAS ANTIMIKROBA PADA INFEKSI SALURAN KEMIH - Fenty Fenty; Syafada Syafada (Sanata Dharma University, 2013)
Abstract: A urinary tract infections (UTI) is an infection that affects the urinary tract caused bybacteria (most often Escherichia coli). Antimicrobial are used to treat UTI. The sensitivity ofbacterial pattern toward antimicrobials and the bacterials pattern will affect the effectiveness ofUTI treatment. This research was conducted to evaluate the strains of bacterial and sensitivity ofbacterial pattern that caused UTI. A descriptive evaluation and retrospective study was done inthis research. In total 79 cases patient with UTI at Inpatient Unit X hospital in Yogyakarta2011, whose has sensitivity test and sprout up germ culture examination data were included.Patient with UTI at Inpatient Unit which has barren germ culture data and sprout up germ wereexcluded. The common microbes were gram negative bacteria including Escherichia col,Pseudomonas aeruginosa, Klebsiella pneumonia, and Staphylococcus coagulase negative.Gram negative microbes were sensitive to amikasin, imipenem, netilmicin, and fosfomicin. Grampositive microbes were sensitive to nitrofurantoin, vancomicin, imipenem and cefuroxime.Keywords: Urinary Tract Infection, antimicrobial, and sensitivity bacterial pattern.